ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN DI MBAK NINGSIH KOSMETIK KABUPATEN TORAJA UTARA - Tirsa Tasik; Isak Pasulu’; Dwibin Kannapadang (Smart Education, 2026)
This study aims to analyze consumer behavior regarding purchase decisions at Mbak Ningsih Cosmetics in North Toraja Regency. The study employs a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that consumer purchase decisions are influenced by product quality, price, service, promotion, and recommendations. These findings are expected to provide valuable insights for Mbak Ningsih Cosmetics in enhancing its marketing strategies and customer satisfaction.